Laparoscopically assisted vaginal hysterectomy in a patient with micro-invasive cervical cancer after two liver transplantations - Tahmasbi Rad, Morva; Wallwiener, Markus; Schemmer, Peter; Schott, Sarah; Sohn, Christof; Rom, Joachim; Eichbaum, Michael H. R. (Journal of obstetrics and gynaecology Canada, 2012)
Background - Advances in surgical techniques and immunosuppressive therapy have improved graft survival in transplant recipients. However, intense long-term immunosuppression increases the incidence of cancer in these patients compared with the general population, not least because of viral infections. Cervical cancer is the third most common malignancy worldwide. In early invasive cervical cancer, surgery is the treatment of choice. - Case - In 2010, we performed a laparoscopically assisted vaginal hysterectomy (LAVH) in a 42-year-old patient with micro-invasive cervical adenocarcinoma (FIGO stage IA1) who had undergone two liver transplantations in 2006 and 2008. The patient was followed up for 18 months after surgery. Despite upper abdominal adhesions and minor difficulties in inserting the Veress needle, the pneumoperitoneum was created safely. The procedure was completed within 157 minutes without any intraoperative complications. Blood loss was less than 100 mL. Postoperative course was uncomplicated with minimal fluctuations in liver function markers. Immunosuppressive therapy was continued without modification. The patient was discharged on postoperative day 9. No complications or recurrence were reported during the 18-month follow-up. - Conclusions - The laparoscopic approach is a justifiable form of surgical management in the treatment of a liver transplant recipient with early-stage cervical cancer. - Résumé - Contexte - Des percées dans les domaines des techniques chirurgicales et de la thérapie immuno-suppressive ont permis l’amélioration de la survie des greffons chez les greffées. Cependant, l’immuno-suppression intense à long terme entraîne une hausse de l’incidence du cancer chez ces patientes, par comparaison avec la population générale, particulièrement en raison d’infections virales. Le cancer du col utérin est la troisième affection maligne en importance à l’échelle mondiale. Dans les cas précoces de cancer invasif du col utérin, la chirurgie constitue le traitement à privilégier. - Cas - En 2010, nous avons mené une hystérectomie vaginale assistée par laparoscopie (HVAL) chez une patiente de 42 ans qui présentait un adénocarcinome cervical micro-invasif (stade FIGO IA1) et qui avait subi deux greffes du foie (en 2006 et en 2008). La patiente a fait l’objet d’un suivi pendant 18 mois à la suite de la chirurgie. Malgré la présence d’adhérences dans la partie supérieure de l’abdomen et de difficultés mineures au moment d’insérer l’aiguille de Veress, le pneumopéritoine a pu être créé en toute sûreté. L’intervention a été accomplie en 157 minutes sans complications peropératoires. La perte sanguine a été inférieure à 100 ml. L’évolution postopératoire s’est avérée exempte de complications et n’a été ponctuée que de fluctuations minimales des marqueurs de la fonction hépatique. La thérapie immuno-suppressive s’est poursuivie sans modification. La patiente a obtenu son congé de l’hôpital neuf jours à la suite de l’intervention. Aucune complication ni récurrence n’ont été signalées au cours des 18 mois de suivi. - Conclusions - L’approche laparoscopique constitue une forme justifiable de prise en charge chirurgicale d’une greffée du foie qui présente un cancer du col utérin en étant à un stade précoce.